PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATA PELAJARAN KELISTRIKAN OTOMOTIF SISWA KELAS XI PROGRAM TEKNIK KENDARAAN RINGAN SMK MUHAMMADIYAH MUNGKID TAHUN AJARAN 2015/2016 - Arif Wijayanto; Arif Bintoro Johan (Universitas Sarjanawiyata Tamansiswa, 2016)
The objective of this research was to improve (1) the activity of automotive electrical subject and (2) the results of automotive electrical study subjects using cooperative learning of jigsaw. The tyep of this study was a classroom action research. The technique of collecting data using questionnaires, tests, and documentation. Data analysis techniques used descriptive qualitative and quantitative. The results showed that (1) the results showed that the activity of study subjects students can increase ignition. Based on the results of the activity of the pre-action consisting of five aspects of the activity obtained an average percentage of 44.3% active students with less category, the averagevalue of student activity on sisklus I is 67.1% with the good category, the average nilia liveliness the second cycle of 86% with a very good category, and the average value of the liveliness of the third cycle of 89% with a very good category. (2) Based on the initial values of students and the results ofevaluation tests conducted in cycle I, II, and III obtained results show an increase. Pratindakan based on test results obtained by 18 students (51.4%) who have not completed the study and 17 students (48.6%) were thoroughly studied by the average value of student ability 63.23. In the first cycle thereare 12 students (34.29%) who have not completed the study and 23 students (65.71%) were thoroughly studied with an average value of 69.67. In the second cycle there were 10 students (28.57%) who have not completed the study and 25 students (71.43%) were thoroughly studied with an average value of 73.42. Based on the test results at the end of the third cycle there are 29 students (82.86%) were thoroughly studied and 6 students (17.14%), which has not been thoroughly studied with an average value of 87.97. Berdasakarn these results, it can be concluded that the right jigsaw method used to improve the activity and student learning outcomes